Incidence and Predictors of Eosinophilic Myocardial Hypersensitivity in Patients Receiving Home Dobutamine. Issue 4 (October 2022) - Dagan, Misha; Lankaputhra, Malanka; Yeung, Timothy; Tee, Su Ling; Bader, Illona; Easton, Kellie; Linton, Ashlee; McLean, Catriona; Taylor, Andrew; Bergin, Peter; Kaye, David M.; Leet, Angeline; et al.
Abstract: We sought to examine incidence and predictors of eosinophilic myocardial hypersensitivity (EMH) in a cohort of patients in the home inotrope program of a quaternary cardiac transplant center. Patients on home inotropes with progression to heart transplantation or ventricular assist device (VAD) between January 2000 and May 2020 were included. EMH was diagnosed by the presence of an interstitial predominate eosinophilic infiltrate within the myocardium by experienced cardiac pathologists. From a cohort of 74 patients, 58% (43) were on dobutamine and 42% (31) were on milrinone. Dobutamine was associated with EMH incidence of 14% (6/43), with zero cases in the milrinone cohort. Mean age was 52 ± 12 years, 22% were female. More than half (62%) were nonischemic dilated cardiomyopathies, the remainder were ischemic cardiomyopathy. Dobutamine dose [250 (200–282) vs. 225 (200–291) μg/min] and duration of therapy [41 (23–79) vs. 53 (24–91) days] was similar between those with and without EMH. Median change in eosinophil count was 0.31 × 10 9 /L in the EMH group compared with only 0.03 × 10 9 /L in the non-EMH cohort, P = 0.02. Increase in peripheral eosinophil count of >0.20 × 10 9 /L demonstrated good discrimination between those with and without EMH, c-statistic 0.83 (95% CI 0.66–1.0). Heart failure hospitalization occurred in 83% of the EMH group versus 59% in the non-EMH group, P = 0.26. Requirement for VAD was significantly higher in the EMH group (83% vs. 41%, P = 0.05). In conclusion, EMH occurred in 14% of patients receiving home dobutamine. Rising eosinophil count should prompt physicians to consider EMH and switch to milrinone to avoid possible escalation to VAD.